2015
DOI: 10.1108/ejim-07-2013-0074
|View full text |Cite
|
Sign up to set email alerts
|

Open innovation actions and innovation performance

Abstract: Access to this document was granted through an Emerald subscription provided by 198285 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(50 citation statements)
references
References 35 publications
1
39
0
1
Order By: Relevance
“…Empirical results from the dynamic probit models reveal positive and significant effects of cooperation with suppliers and HEIs on both types of innovations. Greco et al [79], in their review of empirical evidence on the impact of inbound, outbound, and coupled open innovation practices on firms' innovation performance, concluded that supplier-based and research-institution-based coupled practices (i.e., collaborative ties) uniformly had positive innovation effects in previous empirical studies. Our results from the full sample are consistent with this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical results from the dynamic probit models reveal positive and significant effects of cooperation with suppliers and HEIs on both types of innovations. Greco et al [79], in their review of empirical evidence on the impact of inbound, outbound, and coupled open innovation practices on firms' innovation performance, concluded that supplier-based and research-institution-based coupled practices (i.e., collaborative ties) uniformly had positive innovation effects in previous empirical studies. Our results from the full sample are consistent with this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Table 6 shows the journals that have published two or more articles related to this subject, which are focused on technology, science, sustainable and economic development and the relationship between company, industry, university, government, and business. These results show intersection points regarding the possibilities provided by the open innovation paradigm, such as creating and using technology, by means of input and output of knowledge to improve innovative and interactive capacities and to expand markets [3][4][5][6]. Studies on open innovation indicate that this has an impact on sustainable, social and economic development in society, where, undoubtedly, the educational field can contribute significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Open innovation is characterized by the free transference of knowledge between the different subjects involved, such as universities, companies and the government. Open innovation is characterized as the new imperative to create and take advantage of technology, which assumes that an organization can improve its innovative abilities by means of interacting with other organizations [3]. In addition, it involves helping internal innovation of companies using knowledge input and output using technologies and aiming to expand their markets and become more competitive [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In the increasingly fierce competitive environment, continuous innovation has become crucial for the survival and sustainability of firms [1,2]. However, it is difficult for firms to innovate entirely on their own because of limited resources and capabilities [3] and thus firms need to follow the open innovation paradigm to interact with other organizations [4,5]. Knowledge from universities or research institutes is widely recognized as an essential driver of spurring firm innovation performance [6,7].…”
Section: Introductionmentioning
confidence: 99%